Optimización de cuidados de enfermería postquirúrgicos en histerectomías de mujeres jóvenes - Viteri Llerena, Sandra Elizabeth (2025)
The optimization of post-surgical nursing care in young women undergoing hysterectomy is fundamental due to the physical and emotional implications that this procedure can have on their lives. The aim of the study was to design a comprehensive post-surgical nursing care guide for this population group in Ecuador, using a systematic review of the available literature. We used exhaustive search methods in scientific databases and selected relevant studies that addressed best practices in postoperative hysterectomy care. The main results highlighted the need for a personalized approach that addresses both physical and emotional aspects, underlining the importance of early mobilization, adequate pain management and emotional support to facilitate a faster and more effective recovery. In addition, the lack of specific guidelines adapted to the Ecuadorian context was identified, highlighting the relevance of developing a practical resource to improve the quality of care and well-being of these patients.